2013
DOI: 10.1038/sj.bdj.2012.1176
|View full text |Cite
|
Sign up to set email alerts
|

Adult Dental Health Survey 2009: relationships between dental attendance patterns, oral health behaviour and the current barriers to dental care

Abstract: The importance of understanding barriers to dental attendance of adults in the UK was acknowledged in the first Adult Dental Health Survey in 1968 and has been investigated in all subsequent ADH surveys. In 1968, approximately 40% of dentate adults said they attended for a regular check-up; by 2009 this was 61%. Attendance patterns were associated with greater frequency of toothbrushing, use of additional dental hygiene products, lower plaque and calculus levels. Just under three-fifths of adults said they had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
156
3
8

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(182 citation statements)
references
References 8 publications
15
156
3
8
Order By: Relevance
“…The type of residential area (urban/rural), incidence of dental checkups within a year, smoking and drinking also affected the frequency of tooth brushing, confirming the results of a previous study (24). Reports of tooth brushing frequency vary among different studies (25)(26)(27). A previous study performed in the United Kingdom, with a sample size of 13,400 households, demonstrated that 75% of the population performed twice-daily brushing.…”
Section: Discussionsupporting
confidence: 79%
“…The type of residential area (urban/rural), incidence of dental checkups within a year, smoking and drinking also affected the frequency of tooth brushing, confirming the results of a previous study (24). Reports of tooth brushing frequency vary among different studies (25)(26)(27). A previous study performed in the United Kingdom, with a sample size of 13,400 households, demonstrated that 75% of the population performed twice-daily brushing.…”
Section: Discussionsupporting
confidence: 79%
“…Similar to the inference from this work on oral and pharyngeal cancer, the authors of the previous study state that although they are unable to rule out clinically relevant effects of small magnitude, their study combined with previous literature, ‘provide evidence that population‐wide screening for vitamin D deficiency and subsequent widespread vitamin D supplementation should not currently be recommended as a strategy for primary cancer prevention’. Recent RCTs examining the effect of vitamin D on cancer incidence do not show strong evidence of a protective effect, although these studies are limited to older females 35, 36. Contrary to this, Ong et al 18.…”
Section: Discussionmentioning
confidence: 98%
“…In terms of a relationship between the frequency of daily brushing and regular dental attendance, Sugihara et al found that in a cross-sectional study targeting 211 people between 60 and 98 years of age, cleaning teeth or dentures three or more times per day was one of the associated factors for regular dental attendance [20]. Moreover, Hill et al reported that there was an association between attendance patterns and frequency of tooth brushing [19]. However, there have been few studies about a relationship between the duration of brushing teeth and regular dental attendance.…”
Section: Discussionmentioning
confidence: 99%
“…We selected gender, age and family income as adjustment factors as these factors have been reported to be associated with regular dental attendance [2,4,[6][7][8][9][10][11]. Moreover, work environment [14,15], lifestyle [16][17][18] and oral hygiene behaviour [19,20] were included as questionnaire components because these factors have been reported as factors associated with dental diseases or regular dental attendance. As an indicator of measuring work stress, we picked some components in reference to the English version of the Brief Job Stress Questionnaire created by the Japanese Ministry of Health, Labour and Welfare [21].…”
Section: Questionnaire Componentsmentioning
confidence: 99%